2016
DOI: 10.1140/epjst/e2015-50099-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of renewable energy sources and electric vehicle penetration into energy systems predominantly based on lignite

Abstract: Abstract. We consider an integration of renewable energy into transport and electricity sectors through vehicle to grid (V2G) technologies for an energy system that is predominantly based on lignite. The national energy system of Macedonia is modeled using EnergyPLAN which integrates energy for electricity, transport and heat, and includes hourly fluctuations in human needs and the environment. We show that electric-vehicles can provide the necessary storage enabling a fully renewable energy profile for Macedo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Only two other studies focused on the monetization of health externalities in finding cost optimum penetrations of V2G-capable EVs, both in terms of optimal levels of electrified transportation, but also in that V2G could decrease air pollution emissions from the electricity sector [42,66]. Another study only loosely discussing V2G mentioned air pollution emissions in the context of optimizing charging station site selection for PEVs [67], while a fifth focused on the potential for particulate matter emission reductions purely from a transportation perspective, noting that PEVs could decrease emissions by 34% by 2035 [68]. Yet, none of these papers focused exclusively or even primarily on the health impacts of V2G-capable EVs.…”
Section: Environmental Performancementioning
confidence: 99%
“…Only two other studies focused on the monetization of health externalities in finding cost optimum penetrations of V2G-capable EVs, both in terms of optimal levels of electrified transportation, but also in that V2G could decrease air pollution emissions from the electricity sector [42,66]. Another study only loosely discussing V2G mentioned air pollution emissions in the context of optimizing charging station site selection for PEVs [67], while a fifth focused on the potential for particulate matter emission reductions purely from a transportation perspective, noting that PEVs could decrease emissions by 34% by 2035 [68]. Yet, none of these papers focused exclusively or even primarily on the health impacts of V2G-capable EVs.…”
Section: Environmental Performancementioning
confidence: 99%
“…Regarding a promising way in which climate mitigation may be helped by the closer integration of different infrastructure networks, Heidi Heinrichs and Patrick Jochem [18] use a detailed model of the German energy system to show that electric vehicles can be integrated in the electricity system without increasing the system costs but would substantially contribute to decreasing CO 2 emissions. In another regional study, Aleksandar Dedinec and his co-authors [19] use a model of the national energy system of Macedonia to demonstrate that electric vehicles can provide enough storage for a fully renewable energy system and lead to a vast reduction of car traffic pollution. Since many simulation studies rely on a suitable tradeoff between technical detail and simplicity required for tractability and gaining systemic understanding, Sabine Auer and co-authors [20] studied what impact the amount of detail in models of electricity grid dynamics has on typical measures of stability and resilience and found that for many typical questions, voltage dynamics need not be modelled explicitly in addition to frequency dynamics.…”
mentioning
confidence: 99%